Acceptability of a second lockdown in Western India: anniversary of lockdown one - Bhartiya, Shibal; Kumar, Nishant (International Journal Of Community Medicine And Public Health, 2021)
Background: The aim of the study was to evaluate the knowledge and attitude of the inhabitants of the urban slums in Mumbai, Maharashtra, regarding re-imposition of a lockdown. Methods: This cross-sectional, voluntary, questionnaire-based study was conducted in an urban slum in October, 2020. Questions were designed to elicit responses about COVID-19 awareness, acceptability of lockdown, including travel restrictions, closure of schools, colleges, and places of worship. Median and range were calculated for continuous variables, while categorical variables were represented as frequency and percentages. P value<0.05 was statistically significant. Results: A total of 1342 adult respondents (710 females, 632 males), were included in this questionnaire-based analysis. Most respondents believed awareness about COVID-19 was adequate, the younger population more in agreement with statement. 77.4% of the respondents believed that authorities should restrict travel to and from COVID-19 hotspot areas, while 81% said colleges and schools should be closed. Interestingly, 80.5% of the respondents supported closure of temples and mosques, while 75.7% supported a citywide lockdown with cases rising, and 7.6% were against it. The significant positive associations for lockdown included younger age, higher education, higher and income. Retired people were least likely to agree with the restrictions of a lockdown. Conclusions: While majority of urban slum inhabitants in Mumbai agree with the need for a lockdown in case of increase in COVID-19 cases, it is important to continue culturally targeted risk communication, along with implementation of social justice-oriented policies.